Utilization of Stick Media in Improving Critical Thinking Skills in Spatial Building Material in Grade 4 Elementary School - Maisura; Juniati; Suwarni; Rasyidah; Linawati; Sarwati; Sabitillah, Lisa (Yayasan Citra Dharma Cindekia, 2024)
This study aims to explore the use of stick media in improving critical thinking skills in fourth-grade students on the topic of properties of space figures. The research employs a qualitative case study approach, focusing on how stick media can facilitate students' understanding of geometric concepts and enhance their ability to analyze and evaluate spatial relationships. Data were collected through observations, interviews with teachers and students, and tests measuring critical thinking skills before and after the intervention. The results show that the use of stick media significantly increased students' ability to critically analyze and solve problems related to space figures. This study concludes that stick media is an effective and engaging tool for improving critical thinking skills, especially in mathematics, and provides a concrete learning experience for students to better understand abstract concepts.